Association between live microbe intake and severe headache or migraine: evidence from NHANES 1999–2004 - Xu, Rongjiang; Yu, Xiangmin; Zhang, Ruonan; Xu, Xiaonuo; Fan, Xiaoping; Dong, Liang; Zhou, Jiying (Frontiers in Nutrition, 2025)
ObjectiveThe pathogenesis of migraine is not fully understood until now. This study was designed to explore whether the intake of live dietary microbes could be used as an auxiliary means for the treatment of severe headache and migraine.MethodsData used in this study were came from the US National Health and Nutrition Examination Survey (NHANES) from 1999 to 2004. Participants were divided into three groups according to the dietary live microbe classification system, namely low, medium and high dietary live microbe groups. Weighted logistic regression models were used for statistical analysis.ResultsA total of 13,443 participants were included in the present study. Compared with the low dietary live microorganism group, the migraine OR (95% CI) of medium-high dietary live microorganism group is 0.71 (0.63–0.81) and 0.73 (0.62–0.86), respectively, in the unadjusted model. After fully adjusting for confounding factors, patients in medium-high dietary live microbe group had a lower prevalence of migraine in contrast to those in low dietary live microbe group (Medium OR: 0.79, 95% CI: 0.68–0.93, P = 0.005; High OR: 0.82, 95% CI: 0.67–0.99, P = 0.047).ConclusionOur study shows that a moderate-high intake of live dietary microbes is inversely associated with the prevalence of severe headache or migraine.